Association Between Oral Microbiota Dysbiosis and the Risk of Dementia: A Systematic Review - Alain Manuel Chaple-Gil; Meylin Santiesteban-Velázquez; Joaquín Juan Urbizo Vélez (Dentistry Journal, 2025)
Background/Objectives: Growing evidence suggests that oral microbiota dysbiosis may contribute to the development of systemic conditions, including neurodegenerative diseases. This dysregulation promotes immunoinflammatory responses that are increasingly associated with dementia. This systematic review aimed to evaluate the association between oral microbiota dysbiosis and the risk of dementia in older adults. Methods: Eligible studies evaluated oral microbial composition using validated methods such as genetic sequencing, bacterial culture, or metagenomic analysis. Following PRISMA guidelines and a PICO framework, the review included cohort, case–control, and cross-sectional studies. Searches were conducted across PubMed, Scopus, Web of Science, Embase, and Cochrane Library. Two independent reviewers screened and selected studies, resolving disagreements through a third evaluator. Results: This systematic review revealed that Tannerella forsythia, Fusobacterium nucleatum, Porphyromonas, Prevotella, Leptotrichia, Fusobacteriota, Peptostreptococcaceae, and Candida spp. were consistently associated with Alzheimer’s disease and mild cognitive impairment, indicating their potential role in neurodegeneration. In contrast, Streptococcus gordonii, Gemella haemolysans, Rothia, Neisseria, and Haemophilus were reduced in cognitively impaired individuals, suggesting a link with healthy cognition. Studies also showed decreased microbial diversity in Alzheimer’s disease and the possible modifying effect of the APOE4 allele. Oral health interventions improved microbial composition and slowed cognitive decline, supporting the diagnostic and therapeutic potential of oral microbiota modulation. Conclusions: The findings suggest that oral microbiota dysbiosis may not only result from cognitive decline but also contribute to its pathogenesis. Future studies with larger and more diverse cohorts are recommended to validate these associations.